2023
DOI: 10.3390/ijms24098117
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Based Proteomic Profiling Identifies Potential Biomarker Candidates and Pathogenic Pathways in Dementia

Abstract: Dementia is a progressive and debilitating neurological disease that affects millions of people worldwide. Identifying the minimally invasive biomarkers associated with dementia that could provide insights into the disease pathogenesis, improve early diagnosis, and facilitate the development of effective treatments is pressing. Proteomic studies have emerged as a promising approach for identifying the protein biomarkers associated with dementia. This pilot study aimed to investigate the plasma proteome profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
(88 reference statements)
0
1
0
Order By: Relevance
“… 12 In recent years, several mass spectrometry (MS)–based proteomics profiling studies of CSF and plasma have revealed protein biomarkers and insights into the biological processes underlying AD, with minimum sample amounts and high-throughput workflows. 2 , 13 , 14 , 15 , 16 However, early diagnostic and staging blood-based biomarkers of AD remain incompletely defined.…”
Section: Introductionmentioning
confidence: 99%
“… 12 In recent years, several mass spectrometry (MS)–based proteomics profiling studies of CSF and plasma have revealed protein biomarkers and insights into the biological processes underlying AD, with minimum sample amounts and high-throughput workflows. 2 , 13 , 14 , 15 , 16 However, early diagnostic and staging blood-based biomarkers of AD remain incompletely defined.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this purpose, the review article by Ehtewish and colleagues [8] provides an exhaustive background on the potential risk factors and the underlying mechanisms linking diabetes, cognitive impairment, and dementia. Moreover, these authors discuss the most relevant biomarkers related to cognitive decline in patients with diabetes.…”
mentioning
confidence: 99%